Learning Styles in Science Education a Decade of Research (2012-2022): A Literature Review - Safitri, Fibriyana; Rusdiana, Dadi; Samsudin, Achmad; Widiyatmoko, Arif (Universitas Lambung Mangkurat, 2024)
This study reviews 50 articles on learning styles in science education, focusing on approaches, media, and learning models from 2012-2022. Every single student with different intelligence certainly has a different learning style. Learning styles provide knowledge about various ways of student learning and important information about student preferences; consequently, they can be utilized to optimize student learning processes. Integrating learning styles in the learning process aims to facilitate students with certain learning styles; therefore, their achievements can be improved sharply. The method of this research is SLR (systematic literature review) with the following phases: (1) determining research questions; (2) determining criteria; (3) generating a framework for articles; (4) searching, filtering, and selecting the data; (5) analyzing and interpreting the content of each reviewed article. This study discusses the distribution of research focused on the attributes of the content, the topics covered in the implementation of learning styles in science education, and the characteristics of existing learning style-based learning media. In conclusion, a literature review has been carried out on learning styles in science education.